Mapping of Campus Da'wah and Its Supports for Rejang Lebong as Religious Regency - Lukman Asha (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
This study aims to describe the role of da'wah mapping performed by the faculty of da'wah at IAIN Curup in supporting the program of Rejang Lebong as a religious regency. This study uses a qualitative approach with the data collection techniques are observation, interview, and documentation and the steps in the process of data analysis are carried out by data reduction, data display, and verifying conclusion. The finding obtains that due to support the program of Rejang Lebong as a religious regency, IAIN Curup contributes through the mapping of da'wah such as Safari Jum’at, Safari Ramadhan, and also Jum’at Barokah. In addition, IAIN Curup provides well-programmed guidance for majlis taklim located in some villages in Rejang Lebong Regency.Penelitian ini bertujuan mendeskripsikan pemetaan wilayah dakwah yang dilakukan Fakultas Dakwah IAIN Curup dalam mendukung program pemerintah kabupaten Rejang Lebong yang religius. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi, dan langkah-langkah analisis data dilakukan dengan reduksi data, menampilkan data, dan penarikan kesimpulan. Penelitian menemukan bahwa dalam rangka mendukung program Rejang Lebong sebagai Kabupaten yang religius, IAN Curup memberikan kontribusi melalui pemetaan dakwah seperti Safari Jum’at, Safari Ramadhan, dan juga Jum’at Barokah. IAIN Curup juga melakukan pembinaan secara terprogram pada majlis taklim yang berada di desa-desa di wilayah Kabupaten Rejang Lebong.